Quantitative Elemental Analysis of Alkaline Metals in Environmental Samples using Liquid Electrode Plasma Optical Emission Spectrometer - Hidayanto, Eko; Yamamoto, Takashi; Kawai, Jun (BERKALA FISIKA, 2009)
Element in bottle drinking water, 100% orange juice and coffee and unknown element and concentration in environmental sample were quantitatively analyzed using a portable elemental analyzer of liquid electrode plasma optical emission spectrometer. In order to carry out this purpose, calibration of known element sample was firstly prepared by measuring its emission intensity in various concentrations. Sodium and potassium were commonly detected by this spectrometer, however other elements such as calcium and magnesium were not detected due to the minimum detection limit. The detected element by this portable analyzer shows that its accuracy is enough for quantitative analysis of environmental samples.